Atmospheric CO2 and Sea Surface Temperature Variability Cannot Explain Recent Decadal Variability of the Ocean CO2 Sink. Issue 7 (5th April 2022) - DeVries, Tim
Abstract: The ocean is one of the most important sinks for anthropogenic CO2 emissions. Here, I use an ocean circulation inverse model (OCIM), ocean biogeochemical models, and pCO2 interpolation products to examine trends and variability in the oceanic CO2 sink. The OCIM quantifies the impacts of rising atmospheric CO2, changing sea surface temperatures, and gas transfer velocities on the oceanic CO2 sink. Together, these effects account for an oceanic CO2 uptake of 2.2 ± 0.1 PgC yr −1 from 1994 to 2007, and a net increase in the oceanic carbon inventory of 185 PgC from 1780 to 2020. However, these effects cannot account for the majority of the decadal variability shown in data‐based reconstructions of the ocean CO2 sink over the past 30 years. This implies that decadal variability of the ocean CO2 sink is predominantly driven by changes in ocean circulation or biology that act to redistribute both natural and anthropogenic carbon in the ocean. Plain Language Summary: The ocean currently absorbs about 25% of industrial CO2 emissions, but there are numerous factors that can cause variation in the rate of ocean CO2 uptake over time. This study uses a combination of observation‐based models to investigate the causes of variability in the rate of ocean CO2 uptake. The results show that the long‐term trend of ocean CO2 uptake is driven mainly by increasing atmospheric CO2 concentrations, but the variability from that trend is due mostly to changes in the distribution of CO2 in the ocean that are caused by changes in ocean circulation and biology. Key Points: An ocean circulation inverse model is used to quantify abiotic air‐sea CO2 fluxes from 1780 to 2020 Increasing atmospheric pCO2 drives the multidecadal trend in ocean CO2 uptake, which averages 2.7 PgC yr −1 from 2010 to 2020 Ocean circulation and biology are implicated as the main drivers of decadal variability of the ocean CO2 sink